2022
DOI: 10.3390/diagnostics12020339
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Early Biomarkers Associated with the Development of Critical Respiratory Failure in Coronavirus Disease 2019 (COVID-19)

Abstract: Certain biomarkers predict death due to acute respiratory distress syndrome in COVID-19 patients. We retrospectively analyzed biomarkers associated with time to mechanical ventilation for respiratory failure due to COVID-19 (time-to-mechanical ventilation) in 135 consecutive patients in our hospital. We analyzed biomarkers that were elevated immediately (at admission) and later (3 days after admission) using Cox proportional hazards regression analysis. Independent biomarkers of time-to-mechanical ventilation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…These articles were re-evaluated based on full-text contents, resulting in exclusion of 8 articles. Finally, 15 studies met the inclusion criteria and were included in our meta-analysis ( Figure 1 ) [ 5 , 8 , 12 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. All selected studies were published between 2020 and 2022.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These articles were re-evaluated based on full-text contents, resulting in exclusion of 8 articles. Finally, 15 studies met the inclusion criteria and were included in our meta-analysis ( Figure 1 ) [ 5 , 8 , 12 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. All selected studies were published between 2020 and 2022.…”
Section: Resultsmentioning
confidence: 99%
“…Greater clinical value could be found in using KL-6 at admission to predict the subsequent course of COVID-19. Twelve studies involved in our meta-analysis assessed the KL-6 level according to the disease severity [ 6 , 8 , 14 , 19 , 20 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Our analysis demonstrated that there was a significantly higher level of KL-6 in patients suffering from severe COVID-19 than mild-to-moderate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The release of DAMPs to extracellular spaces is a characteristic of necrosis that distinguishes it from apoptosis 58 . Several previous studies have also reported that circulating levels of DAMPs, such as HMGB-1 [59][60][61][62] , histone 62,63 , cell free-DNA 62,63 , mitochondrial DNA [64][65][66] and S100 proteins 67,68 are elevated in severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…9,21 The PT results showed a non-significant difference, which was consistent with a previous study that reported a normal PT values. 1 The INR mean values indicated a significant decrease in COVID-19 12,13,31,37 Study limitations. A number of coagulation parameters, including factor V111, fibrinogen, thrombin time, and Von Willebrand factor, were not included due to their absence in the routine laboratory investigation for our COVID-19 patients' study group, so it is highly recommended for further studies to include all the coagulation-related parameters.…”
mentioning
confidence: 92%